Delivery of the research participant perception survey through the patient portal - Kelly-Pumarol, Issis J. (J Clin Transl Sci, 2018)
INTRODUCTION: The patient portal may be an effective method for administering surveys regarding participant research experiences but has not been systematically studied. METHODS: We evaluated 4 methods of delivering a research participant perception survey: mailing, phone, email, and patient portal. Participants of research studies were identified (n=4013) and 800 were randomly selected to receive a survey, 200 for each method. Outcomes included response rate, survey completeness, and cost. RESULTS: Among those aged <65 years, response rates did not differ between mail, phone, and patient portal (22%, 29%, 30%, p>0.07). Among these methods, the patient portal was the lowest-cost option. Response rates were significantly lower using email (10%, p<0.01), the lowest-cost option. In contrast, among those aged 65+ years, mail was superior to the electronic methods (p<0.02). CONCLUSIONS: The patient portal was among the most effective ways to reach research participants, and was less expensive than surveys administered by mail or telephone.